1. The simplified expression is 10x+8y-12.
Combine like terms to simplify the expression.
-6x-12+8y+16x
-6x and 16x are both like terms, so those can be combined.
-6x+16x=10x
10x+8y-12
2. The solution to the equation is x=13.
Solve by adding 17 to both sides of the equation.
-4=-17+x
-4+17=-17+17+x
13=x
Multiply the dimensions by 3 to convert to feet.
12 x 3 = 36 ft.
15 x 3 = 45 ft.
the dimensions are 36 ft. x 45 ft.
Answer:
AB = 3
Step-by-step explanation:
AB = AD
AB² + 4² = (AB + 2)²
AB² + 16 = AB² + 4AB + 4
combine like terms:
4AB = 12
AB = 3
Answer:
<h2>
<em><u>-120</u></em></h2>
Step-by-step explanation:
4(-5)(-2)(-3)
= -20 × 6
= <em><u>-120 (Ans)</u></em>